Стан вуглеводного обміну та чутливість до інсуліну у хворих на акромегалію з конкомітантною гіперпролактинемією - Микитюк, М. Р.; Хижняк, О. О.; Сулима, Т. Н. (Clinical Endocrinology and Endocrine Surgery, 2012)
Iinvestigation state of carbohydrate methabolism and insulin sensitivity was done in patients with acromegalia with concomitant hyperprolactinemia. The disturbance of carbohydrate metabolism was diagnosed at 43 % patients including 32.7 % with diabetes mellitus. Frequency and structure of carbohydrate metabolism in patient with acromegaly does not depend on concomitant hyperprolactinemia. Effects of growth hormone, prolactin and insulin-like growth factor-1 on carbohydrate metabolism and insulin sensitivity were deternined due to analysis of associations of those factors with basic indexes of carbohydrate metabolism. Level of growth hormone and duration of its pathological influence define stage of disturbance of carbohydrate metabolism at patients with acromegalia.